The Role of Open Land Spaces in Solving the Problem of Lack of Green Areas - Al-Bishari, Yahya Mohammed; Almadhaji, Mohammed Sallam (University of Science and Technology, Yemen, 2019)
Sana'a city suffers from a sever lack of green land spaces since per capita green land spaces is 0.176 m2, it is estimated at less than 1% of the different land uses in the city. The percentage and green land spaces continue to decline due to the continued increasing of population and expansion of the urban blocks of the city. This study aims at solving the problem of lack of green land spaces and upgrading the environmental level of the city of Sana'a by suggesting a vision to increase the percentage of green land spaces as well as per capita in the city. That can be achieved by using the recent wide open land spaces which are available and not used in the city. To achieve this aim, the methodology adopted was analytical, descriptive, and comparative of green lands and their types in cities. It also compared the planning standards with advanced cities and the recent situation of Sana'a city by analytical, descriptive, and comparative studies for open lands and green spaces. The study resulted in some suggestions for solving the problem of lack of green land spaces and increasing the per capita in Sana`a city and thus reached conclusions and recommendations. Keywords: green land spaces, per capita, Sana'a city.